(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract. The landscape of education is continually evolving, driven by the need for innovative approaches to enhance student engagement and learning outcomes. This paper explores the integration of innovative educational practices and the refinement of mechanisms that support independent student work. By examining various pedagogical strategies, including technology-enhanced learning, collaborative projects, and personalized learning pathways, this study identifies effective methods for fostering autonomy and motivation among students. The findings reveal that innovative educational mechanisms significantly improve students' independent work performance, leading to better academic results and higher levels of satisfaction. This paper concludes by offering recommendations for educators and institutions aiming to implement these innovative practices